Method for homogenizing current collector of cathode-free metal battery

By soaking the current collector in diluted hydrochloric acid in the negative electrode-free metal battery to form a homogeneous chlorine atomic layer, the problem of the heterogeneity of the current collector surface hindering the metal ion deposition/dissolution efficiency is solved, and the development of efficient metal ion deposition/dissolution and high-energy density batteries is achieved.

CN119710662APending Publication Date: 2025-03-28WUHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411829427.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In negative electrode-free metal cells, the heterogeneity of the current collector surface hinders the Coulomb efficiency of metal ions deposition/dissolution, resulting in low energy density.

Method used

By soaking the current collector in diluted hydrochloric acid, the heterogeneous material on the surface is removed and a homogenized chlorine atomic layer of atomic thickness is formed, thereby promoting the three-dimensional diffusion and uniform deposition of metal ions and suppressing side reactions.

Benefits of technology

The Coulomb efficiency of metal ions deposition/dissolution in negative electrode-free metal batteries is improved, the reversibility of deposition/dissolution is enhanced, and the development of high energy density is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710662A_ABST
    Figure CN119710662A_ABST
Patent Text Reader

Abstract

The invention provides a method for homogenizing a current collector of a cathode-free metal battery, and belongs to the technical field of energy storage batteries. The current collector with a homogenized chlorine atom layer on the surface is obtained by soaking the current collector in diluted hydrochloric acid and then washing and blow-drying the current collector. The homogenized chlorine atom layer with the atomic-scale thickness on the surface of the current collector can improve the coulombic efficiency of metal ion deposition / dissolution, so that the problems of low coulombic efficiency, poor stability and the like of metal ion deposition / dissolution on the negative electrode side of the current collector of the non-negative electrode metal battery are further solved; according to the current collector with the homogenized chlorine atom layer on the surface, the preparation process is simple, the process conditions are controllable, large-area preparation can be realized, and the large-scale and industrial development of a high-energy-density non-negative-electrode metal battery can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy storage batteries, and in particular to a method for homogenizing a current collector of a negative-electrode-free metal battery. Background Art

[0002] Negative electrode metal-free batteries can effectively solve the problem of low energy density of metal batteries due to low utilization of negative electrode metals, and are a strong candidate for the next generation of high energy density batteries. In negative electrode metal-free batteries, all metal sources come from positive electrode materials and are deposited / dissolved on the negative electrode side, which makes the coulombic efficiency of metal ion deposition / dissolution on the negative electrode current collector side very important.

[0003] The current collector is the most common negative electrode of negative electrode-free metal batteries due to its good mechanical properties and conductivity, but its surface heterogeneity hinders the development of the current collector. Therefore, it is crucial to develop a negative electrode current collector that can improve the coulombic efficiency of metal ion deposition / dissolution. Summary of the invention

[0004] In view of the deficiencies of the above prior art, the present invention provides a method for homogenizing a current collector of a metal-free negative electrode battery. The present invention is based on acid treatment of the current collector, and removes the heterogeneous materials on its surface while forming a homogenized chlorine atom layer with atomic thickness; in the process of metal ion deposition in the metal-free negative electrode battery based on the current collector with the homogenized surface, the homogenized surface can allow the metal ions to diffuse and nucleate in three dimensions, which is conducive to the uniform deposition of metal ions; and the current collector with a homogenized chlorine atom layer on the surface can also inhibit side reactions related to the electrolyte and improve the deposition / dissolution coulomb efficiency of metal ions.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] In a first aspect, the present invention provides a method for homogenizing a current collector of a negative electrode metal-free battery, comprising mixing concentrated hydrochloric acid and water in a certain volume ratio to obtain diluted hydrochloric acid, soaking the current collector in the diluted hydrochloric acid, and rinsing and drying to obtain a current collector having a homogenized chlorine atom layer on the surface;

[0007] Wherein, the volume ratio of the concentrated hydrochloric acid to water is 1:(1-8).

[0008] The present invention uses a hydrochloric acid solution of a specific concentration to immerse the current collector, and while removing the heterogeneous materials on the surface thereof, a uniform, atomic-level thick chlorine atomic layer is formed to induce the deposition behavior of metal ions in the negative electrode-free metal battery. The atomic-level thick homogenized chlorine atomic layer in the present invention neither significantly increases the thickness of the current collector nor induces the uniform deposition of metal ions. In the negative electrode-free metal battery based on the current collector with the homogenized surface, the homogenized chlorine atomic layer can allow the metal ions to diffuse and nucleate in three dimensions during the deposition of metal ions, which is beneficial to the uniform deposition of metal ions. At the same time, the homogenized current collector can also inhibit side reactions related to the electrolyte, thereby achieving high metal ion deposition / dissolution coulomb efficiency in the negative electrode-free metal system.

[0009] Furthermore, the volume ratio of concentrated hydrochloric acid to water is 1:4.

[0010] Furthermore, the concentrated hydrochloric acid is a hydrochloric acid solution with a concentration of 36% to 38%.

[0011] Furthermore, the current collector is selected from one of copper foil, aluminum foil, titanium foil and carbon cloth.

[0012] Furthermore, the current collector is copper foil.

[0013] Furthermore, the current collector is immersed in the diluted hydrochloric acid for 1 to 15 minutes.

[0014] Furthermore, the current collector is immersed in the diluted hydrochloric acid for 5 minutes.

[0015] Furthermore, the flushing is performed with ethanol; flushing the current collector soaked in diluted hydrochloric acid with ethanol is to wash away residual acid.

[0016] Furthermore, the flushing is performed 1 to 5 times.

[0017] Furthermore, the flushing is performed 5 times.

[0018] Furthermore, the drying is carried out by blowing with an inert gas.

[0019] Furthermore, the method for homogenizing the current collector of the negative electrode metal-free battery specifically comprises the following steps:

[0020] (1) Take concentrated hydrochloric acid and mix it with water in a volume ratio of 1:(1-8) to obtain diluted hydrochloric acid;

[0021] (2) Soak the current collector in diluted hydrochloric acid for 1 to 15 minutes;

[0022] (3) rinsing the current collector soaked in acid in step (2) with ethanol at least once;

[0023] (4) The current collector rinsed with ethanol in step (3) is blown dry with an inert gas to obtain a current collector having a homogenized chlorine atom layer on the surface.

[0024] In a second aspect, the present invention provides a current collector having a homogenized chlorine atom layer on its surface obtained by treatment using the method.

[0025] In a third aspect, the present invention provides the use of the current collector having a homogenized chlorine atom layer on the surface in a negative electrode-free metal battery.

[0026] In a fourth aspect, the present invention provides a negative electrode-free metal battery, comprising a current collector having a homogenized chlorine atom layer on its surface and a metal sheet.

[0027] Furthermore, the current collector having a homogenized chlorine atom layer on its surface is a disc with a diameter of 10 mm to 16 mm.

[0028] Furthermore, the current collector having a homogenized chlorine atomic layer on its surface is a disc with a diameter of 16 mm.

[0029] Furthermore, the metal sheet is selected from one of lithium sheet, sodium sheet, potassium sheet and zinc sheet.

[0030] Furthermore, the metal sheet is a zinc sheet with a diameter of 12 mm.

[0031] Compared with the prior art, the present invention is beneficial in that:

[0032] 1. The present invention removes the non-homogeneous layer on the surface of the current collector by immersing the current collector in hydrochloric acid of a certain concentration, and forms a homogenized chlorine atom layer at the same time, so that in the negative electrode-free metal battery based on the present invention, metal ions can be three-dimensionally diffused and uniformly deposited, and the occurrence of side reactions can be avoided, which can greatly improve the reversibility of metal ion deposition / dissolution in the negative electrode-free metal battery.

[0033] 3. The present invention provides a method for homogenizing the current collector of a negative electrode-free metal battery. The process is simple, the process conditions are controllable, and it can be prepared on a large scale, which can promote the large-scale and industrial development of high energy density negative electrode-free metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the copper foil having a homogenized chlorine atomic layer on the surface obtained by the treatment in Example 1;

[0035] Figure 2 This is a time-of-flight secondary mass spectrum of the copper foil having a homogenized chlorine atomic layer on the surface obtained by the treatment in Example 1;

[0036] Figure 3The optical images of the copper foil having a homogenized chlorine atomic layer on the surface obtained by the treatment in Example 1 and the commercial copper foil at different deposition times under the same current;

[0037] Figure 4 The asymmetric cell assembled from the copper foil with a homogenous chlorine atomic layer on the surface obtained in Example 1 and zinc was tested at 10 mA cm -2 The current density is 1 mAh cm -2 Electrochemical performance diagram under capacity;

[0038] Figure 5 The copper foil with a homogenized chlorine atomic layer on the surface obtained in Example 1 and the commercial copper foil at 20 mA cm -2 The current density is 10 mAh cm -2 Physical picture under the capacity;

[0039] Figure 6 The full battery assembled with the copper foil having a homogenized chlorine atomic layer on the surface obtained in Example 1 and manganese dioxide at 1 A g -1 Electrochemical performance diagram at current density of ;

[0040] Figure 7 The asymmetric battery assembled from copper foil and zinc obtained by dilute sulfuric acid treatment in Comparative Example 1 was 10 mA cm -2 The current density is 1 mAh cm -2 Cyclic performance diagram under capacity;

[0041] Figure 8 The asymmetric battery assembled from copper foil and zinc obtained by dilute acetic acid treatment in comparative example 2 was 10 mA cm -2 The current density is 1 mAh cm -2 Cyclic performance diagram under capacity;

[0042] Fig. 9 The asymmetric battery assembled with copper foil and zinc obtained by treating with more dilute hydrochloric acid (concentrated hydrochloric acid: water = 1:10) in Comparative Example 3 was 10 mA cm -2 The current density is 1 mAh cm -2 Cycling performance diagram under capacity. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The present invention provides a method for homogenizing a current collector of a negative electrode metal-free battery, comprising mixing concentrated hydrochloric acid and water in a certain volume ratio to obtain diluted hydrochloric acid, soaking the current collector in the diluted hydrochloric acid, and rinsing and drying the current collector to obtain a current collector having a homogenized chlorine atom layer on the surface;

[0045] Wherein, the volume ratio of the concentrated hydrochloric acid to water is 1:(1-8).

[0046] In some examples, the current collector is selected from one of copper foil, aluminum foil, titanium foil, and carbon cloth.

[0047] In some examples, the current collector is immersed in the diluted hydrochloric acid for 1 to 15 minutes.

[0048] In some examples, the flushing is performed 1 to 5 times.

[0049] In the following specific examples, unless otherwise specified, the concentrated hydrochloric acid is a hydrochloric acid solution with a concentration of 36% to 38%; the concentrated hydrochloric acid is a conventional commercial product.

[0050] Example 1

[0051] A negative electrode-free metal battery based on a current collector with a homogenized chlorine atomic layer on its surface

[0052] (1) Take 5 mL of concentrated hydrochloric acid and mix it with 20 mL of deionized water to obtain diluted hydrochloric acid;

[0053] (2) Soaking the commercial copper foil in the diluted hydrochloric acid prepared in step (1) for 5 minutes;

[0054] (3) Rinse the copper foil soaked in the diluted hydrochloric acid in step (2) with ethanol five times to fully wash away the residual hydrochloric acid;

[0055] (4) drying the copper foil obtained in step (3) with nitrogen to obtain a copper foil having a homogenized chlorine atomic layer on the surface;

[0056] (5) Punching the copper foil obtained in step (4) into a disc with a diameter of 16 mm, and assembling an asymmetric battery with a zinc sheet with a diameter of 12 mm;

[0057] (6) In the cell assembled in step (5), 10 mA cm -2 The current density of 1 mAh cm -2 of zinc onto the copper foil and then at 10 mA cm -2 The asymmetric battery was charged to 0.5 V at a current density of 1.54 Å and the coulombic efficiency was tested.

[0058] Comparative Example 1

[0059] (1) Take 5 mL of concentrated sulfuric acid and mix it with 20 mL of deionized water to obtain diluted sulfuric acid;

[0060] (2) Soaking the commercial copper foil in the diluted sulfuric acid prepared in step (1) for 5 minutes;

[0061] (3) Rinse the copper foil soaked in diluted sulfuric acid in step (2) with ethanol five times to fully wash away the residual sulfuric acid;

[0062] (4) drying the copper foil obtained in step (3) with nitrogen;

[0063] (5) Punching the copper foil obtained in step (4) into a disc with a diameter of 16 mm, and assembling an asymmetric battery with a zinc sheet with a diameter of 12 mm;

[0064] (6) In the cell assembled in step (5), 10 mA cm -2 The current density of 1 mAh cm -2 The zinc was deposited onto the copper foil and then 10 mA cm -2 The asymmetric battery was charged to 0.5 V at a current density of 1.54 Å and the coulombic efficiency was tested.

[0065] Comparative Example 2

[0066] (1) Take 5 mL of acetic acid and mix it with 20 mL of deionized water to obtain diluted acetic acid;

[0067] (2) Soaking the commercial copper foil in the diluted acetic acid prepared in step (1) for 5 minutes;

[0068] (3) Rinse the copper foil soaked in the diluted acetic acid in step (2) with ethanol five times to fully wash away the residual acetic acid;

[0069] (4) drying the copper foil obtained in step (3) with nitrogen;

[0070] (5) Punching the copper foil obtained in step (4) into a disc with a diameter of 16 mm, and assembling an asymmetric battery with a zinc sheet with a diameter of 12 mm;

[0071] (6) In the cell assembled in step (5), 10 mA cm -2 The current density of 1 mAh cm -2 The zinc was deposited onto the copper foil and then 10 mA cm -2 The asymmetric battery was charged to 0.5 V at a current density of 1.54 Å and the coulombic efficiency was tested.

[0072] Comparative Example 3

[0073] (1) Take 2 mL of concentrated hydrochloric acid and mix it with 20 mL of deionized water to obtain dilute hydrochloric acid;

[0074] (2) Soaking the commercial copper foil in the dilute hydrochloric acid prepared in step (1) for 5 min;

[0075] (3) Rinse the copper foil soaked in dilute hydrochloric acid in step (2) with ethanol five times to fully wash away the residual hydrochloric acid;

[0076] (4) drying the copper foil obtained in step (3) with nitrogen;

[0077] (5) Punching the copper foil obtained in step (4) into a disc with a diameter of 16 mm, and assembling an asymmetric battery with a zinc sheet with a diameter of 12 mm;

[0078] (6) In the cell assembled in step (5), 10 mA cm -2 The current density of 1 mAh cm -2 of zinc onto the copper foil and then at 10 mA cm -2 The asymmetric battery was charged to 0.5 V at a current density of 1.54 Å and the coulombic efficiency was tested.

[0079] The relevant characterization and test data of the copper foil with a homogenized chlorine atomic layer on the surface obtained by the treatment of Example 1 and the asymmetric battery assembled thereon, and the asymmetric battery assembled thereon obtained by the treatment of Comparative Examples 1 to 3 are as follows:

[0080] Figure 1 This is a scanning electron microscope image of the copper foil having a homogenized chlorine atomic layer on the surface obtained by the treatment in Example 1. Figure 1 It can be seen that after being treated with a certain concentration of hydrochloric acid, the morphology of the copper foil surface did not change significantly, indicating that the change was at the atomic level.

[0081] Figure 2 This is a time-of-flight secondary mass spectrum of the copper foil having a homogenized chlorine atomic layer on its surface obtained by the treatment in Example 1. Figure 2 It can be seen that after being treated with hydrochloric acid of a certain concentration, an ultra-thin homogenized chlorine atom layer exists on the surface of the copper foil. This homogenized structure helps the three-dimensional diffusion of zinc ions and inhibits the formation of dendrites, thereby improving the cycle stability of the battery.

[0082] Figure 3 The optical images of the copper foil with a homogenized chlorine atomic layer on the surface obtained by the treatment in Example 1 and the commercial copper foil at different deposition times under the same current. Figure 3 It can be seen that the copper foil of the present invention has a -2At a current density of , uniform zinc deposition was formed on the surface after deposition for 0.5 h, 1 h, and 2 h, respectively; while the surface of commercial copper foil showed aggregated zinc deposition. This result shows that the homogenized chlorine atomic layer on the surface of the current collector of the present invention is conducive to the uniform deposition of zinc.

[0083] Figure 4 The asymmetric cell assembled from the copper foil with a homogenous chlorine atomic layer on the surface obtained in Example 1 and zinc was tested at 10 mA cm -2 The current density is 1 mAh cm -2 Electrochemical performance diagram at the capacity of Figure 4 It can be seen that the asymmetric battery assembled from the copper foil and zinc sheet of the present invention has a high -2 The current density is 1 mAh cm -2 The battery can be stably cycled for more than 7,400 cycles at a capacity of 1.5 MW and has a coulombic efficiency of up to 99.90%. However, the asymmetric battery assembled with commercial copper foil failed after less than 500 cycles. This result shows that the treatment method of the present invention can fundamentally improve the reversibility of zinc deposition / dissolution, thereby improving the cycle stability of the battery.

[0084] Figure 5 The copper foil with a homogenized chlorine atomic layer on the surface obtained in Example 1 and the commercial copper foil at 20 mA cm -2 The current density is 10 mAh cm -2 Actual picture of the capacity. Figure 5 It can be seen that no bubbles are generated on the surface of the copper foil of the present invention, while bubbles are generated on the surface of the commercial copper foil. This result shows that the homogenized chlorine atomic layer on the surface of the copper foil of the present invention can inhibit side reactions related to water and improve the stability of the negative electrode-free zinc metal battery system.

[0085] Figure 6 The full battery assembled with the copper foil having a homogenized chlorine atomic layer on the surface obtained in Example 1 and manganese dioxide at 1 A g -1 Electrochemical performance diagram at current density of . Figure 6 It can be seen that the full battery assembled from the copper foil and manganese dioxide of the present invention has a high conductivity at 1 A g -1 After 500 cycles at a current density of , the capacity retention rate is as high as 80%; while the full battery assembled with commercial copper foil has only less than 100 cycles, and its capacity retention rate decays to 20%. This result shows that the treatment of the current collector by the method of the present invention can effectively improve the cycle stability of the battery, and has great commercial application prospects in negative electrode metal-free batteries.

[0086] Figure 7The asymmetric battery assembled from copper foil and zinc obtained by dilute sulfuric acid treatment in Comparative Example 1 was 10 mA cm -2 The current density is 1 mAh cm -2 Cyclic performance diagram under the capacity of. Figure 7 It can be seen that the asymmetric battery failed after less than 250 cycles.

[0087] Figure 8 The asymmetric battery assembled from copper foil and zinc obtained by dilute acetic acid treatment in comparative example 2 was 10 mA cm -2 The current density is 1 mAh cm -2 Cyclic performance diagram under the capacity of. Figure 8 It can be seen that the asymmetric battery failed after only 100 cycles.

[0088] Fig. 9 The asymmetric battery assembled with copper foil and zinc obtained by treating with more dilute hydrochloric acid (concentrated hydrochloric acid: water = 1:10) in Comparative Example 3 was 10 mA cm -2 The current density is 1 mAh cm -2 Cyclic performance diagram under the capacity of. Fig. 9 It can be seen that the asymmetric battery failed after less than 1,500 cycles.

[0089] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A method for homogenizing a current collector of a negative electrode metal-free battery, characterized in that: Concentrated hydrochloric acid and water are mixed in a certain volume ratio to obtain diluted hydrochloric acid, and the current collector is immersed in the diluted hydrochloric acid, and after rinsing and drying, a current collector having a homogenized chlorine atom layer on the surface is obtained; Wherein, the volume ratio of the concentrated hydrochloric acid to water is 1:(1-8).

2. The method for homogenizing a current collector of a negative electrode-free metal battery according to claim 1, characterized in that: The volume ratio of the concentrated hydrochloric acid to water is 1:

4.

3. The method for homogenizing a current collector of a negative electrode-free metal battery according to claim 1, characterized in that: The current collector is immersed in the diluted hydrochloric acid for 1 to 15 minutes.

4. The method for homogenizing a current collector of a negative electrode metal-free battery according to claim 3, characterized in that: The current collector is immersed in the diluted hydrochloric acid for 5 minutes.

5. The method for homogenizing a current collector of a negative electrode metal-free battery according to claim 1, characterized in that: The current collector is selected from copper foil, aluminum foil, titanium foil and carbon cloth.

6. The method for homogenizing a current collector of a negative electrode-free metal battery according to claim 5, characterized in that: The current collector is copper foil.

7. A current collector having a homogenized chlorine atomic layer on its surface obtained by treatment with the method according to any one of claims 1 to 6.

8. Use of the current collector having a homogenized chlorine atom layer on the surface as claimed in claim 7 in a negative electrode-free metal battery.

9. A negative electrode metal-free battery, characterized in that: It comprises a current collector having a homogenized chlorine atom layer on its surface as described in claim 7 and a metal sheet.

10. A negative electrode-free metal battery according to claim 9, characterized in that: The metal sheet is selected from one of lithium sheet, sodium sheet, potassium sheet and zinc sheet.